2017
DOI: 10.4102/sajhrm.v15i0.683
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between demographic variables and well-being of women in South African workplaces

Abstract: Orientation: It is important to investigate the determinants of well-being among working women. Given the unique demographic diversity within the South African context, differences in the experience of well-being among women are expected.Purpose: The study investigated the effects of age, race, marital status and educational status on psychological meaningfulness, life satisfaction, work–family conflict and social support of working women.Motivation: With the increase of women in the workplace, there is a need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
(154 reference statements)
0
8
1
Order By: Relevance
“…Their study found that female and male groups were of similar levels for work engagement and FWC; however, in terms of WFC, female physicians reported higher levels of conflict. In addition to this, Geldenhuys and Henn (2017) found, in their study of women in South African workplaces, that a significant relationship exists between life satisfaction, WFC, and work engagement. Moreover, being White showed a significant positive relationship with life satisfaction, WFC, and work engagement.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Their study found that female and male groups were of similar levels for work engagement and FWC; however, in terms of WFC, female physicians reported higher levels of conflict. In addition to this, Geldenhuys and Henn (2017) found, in their study of women in South African workplaces, that a significant relationship exists between life satisfaction, WFC, and work engagement. Moreover, being White showed a significant positive relationship with life satisfaction, WFC, and work engagement.…”
Section: Resultsmentioning
confidence: 90%
“…Three studies (see Y. S. Chen & Huang, 2016; Li et al, 2014; Simbula, 2010) found that social or colleague support is the precondition for either work engagement or WFC. When it comes to the outcomes of both work engagement and WFC, the most frequently studied outcome was satisfaction, including job satisfaction (i.e., Burke et al, 2013; Mache et al, 2016; Simbula, 2010), family satisfaction (i.e., Ilies et al, 2017; Timms et al, 2015), and personal or life satisfaction (i.e., Geldenhuys & Henn, 2017; Scanlan et al, 2013). Seven studies, including those by Burke et al (2013) and Mache et al (2016), found a positive association between satisfaction as an outcome variable and work engagement and WFC, while the factors of satisfaction, turnover intention, and intention to stay were also notable outcomes highlighted in three studies by Burke et al (2013), Dåderman and Basinska (2016), and Scanlan et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Since income and further education always influence level of satisfaction (Fernández-Ballesteros, (2001); Geldenhuys & Henn, 2017) organizational support, in this case from the School Foundation and local government are needed to manage about income policies, and health protection. Teacher's career plan and sustainability of the school has a crucial role of teachers' life satisfaction.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Since well-being at work impacts on work performance and quality of life, knowledge about the profile of well-being at work is essential to improve the working environment and reduce NCD and turnover of nutritionists [5]. Work-related well-being can affect individuals differently, and it is essential to consider socioeconomic and demographic factors approaching when stressrelated issues [34][35][36]. Structural inequalities and differences in socio-demographic issues may also affect well-being at work [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Work-related well-being can affect individuals differently, and it is essential to consider socioeconomic and demographic factors approaching when stressrelated issues [34][35][36]. Structural inequalities and differences in socio-demographic issues may also affect well-being at work [34][35][36].…”
Section: Introductionmentioning
confidence: 99%